2014
DOI: 10.18632/oncotarget.2328
|View full text |Cite
|
Sign up to set email alerts
|

The iron chelator Dp44mT inhibits hepatocellular carcinoma metastasis via N-Myc downstream-regulated gene 2 (NDRG2)/gp130/STAT3 pathway

Abstract: Here we showed that hepatocellular carcinoma (HCC) cell lines with high metastatic potential had low levels of NDRG2. The iron chelator Dp44mT up-regulated NDRG2, suppressed epithelial-mesenchymal transition (EMT) and inhibited tumor metastasis in HCC having high metastatic potential. Also Dp44mT attenuated the TGF-β1-induced EMT in HCC having low metastatic potential. In agreement, silencing endogenous NDRG2 with shNDRG2 in HCC cells attenuated the effect of Dp44mT. We showed that the NDRG2/gp130/STAT3 pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 41 publications
2
76
1
Order By: Relevance
“…Previous studies from our laboratory and others have indicated that novel di-2-pyridylketone thiosemicarbazones (i.e., Dp44mT and DpC) markedly inhibit tumor growth and metastasis both in vitro and in vivo (Yuan et al, 2004;Kovacevic et al, 2011b;Liu et al, 2012;Lovejoy et al, 2012;Wang et al, 2014). Intriguingly, these agents also markedly upregulate NDRG1 expression, with this effect being mediated by iron depletion via HIF-1a-dependent and -independent mechanisms (Le and Richardson, 2005;Kovacevic et al, 2011a;Lovejoy et al, 2012;Fang et al, 2014).…”
Section: Ndrg1 Inhibits Fak/paxillin Pathway In Cancer Cellsmentioning
confidence: 86%
“…Previous studies from our laboratory and others have indicated that novel di-2-pyridylketone thiosemicarbazones (i.e., Dp44mT and DpC) markedly inhibit tumor growth and metastasis both in vitro and in vivo (Yuan et al, 2004;Kovacevic et al, 2011b;Liu et al, 2012;Lovejoy et al, 2012;Wang et al, 2014). Intriguingly, these agents also markedly upregulate NDRG1 expression, with this effect being mediated by iron depletion via HIF-1a-dependent and -independent mechanisms (Le and Richardson, 2005;Kovacevic et al, 2011a;Lovejoy et al, 2012;Fang et al, 2014).…”
Section: Ndrg1 Inhibits Fak/paxillin Pathway In Cancer Cellsmentioning
confidence: 86%
“…These agents were also demonstrated to broadly inhibit a number of oncogenic pathways via NDRG1-dependent mechanisms, including TGF-␤, WNT, PI3K, etc. (4,6,18,25).…”
Section: In the Presence Of Egf Ndrg1 Inhibits Formation Of The Egfrmentioning
confidence: 99%
“…Moreover, these thiosemicarbazones possessed potent and selective anti-cancer activity against a range of tumors both in vitro and in vivo (1,3,(21)(22)(23)25). The potential of these novel compounds is underscored by their marked ability to inhibit tumor cell metastasis in vivo (18) and overcome cancer cell multidrug resistance mediated by P-glycoprotein in vitro and in vivo (23,26).…”
mentioning
confidence: 99%
“…Furthermore, Dp44mT and the structurally similar thiosemicarbazone, di-2-pyridylketone 4-cyclohexyl-4-methyl-3-thiosemicarbazone (DpC; Fig. 1Aiii), have demonstrated marked anti-tumor and anti-metastatic activity in vitro and in vivo (15)(16)(17)(18)(19)(20). Notably, DpC is expected to enter clinical trials by the end of 2016.…”
Section: Multidrug Resistance (Mdr)mentioning
confidence: 99%